IMPLEMENTASI PENGELOLAAN KEUANGAN DESA PADA APBDES DI DESA PENARA KEBUN KECAMATAN TANJUNG MORAWA - Dito Aditia Darma Nasution (UNIVERSITAS PEMBANGUNAN PANCA BUDI, 2020)
The phenomena and problems in managing village finances can be seen in the implementation in the Village Revenue and Expenditure Budget which implementation is not in accordance with the provisions of Permendagri 113 of 2014 concerning village financial. The purpose of this study was to determine the reality of the implementation of financial management of the village of Penara Kebun in Tanjung Morawa District, Deli Serdang Regency based on Permendagri 113 of 2014 on village financial management. The research is descriptive with a qualitative approach, research data obtained through in-depth interviews, observation, and documentation studies. This study was analyzed using the Case Study method. The results of the study indicate that the Penara Kebun Village has not fully complied with the provisions of the regulation in financial management during the implementation of the Village Revenue and Expenditure Budget. This requires synergy between the district and sub-district governments in terms of assistance and supervision of village finance providers.